Redefinition of Japanese Culture and Structure of Feelings in Kubo and the Two Strings - Tsaqila Idzhan Nur Rahmah; Erlan Aditya Ardiansyah; Dian Nurrachman (Journal of English Language Teaching and Literature)
This research aims to reveal how Japanese culture is being redefined as a dynamic social process. The social dynamic processes involve emotional experiences that are formed from individual perspectives into collective feelings. It views culture as something that continues to develop along with social changes and the collective feelings felt by society. These ideas are represented in the film Kubo and the Two Strings (2016). This research uses a qualitative approach to Marxist literary criticism. The film Kubo and the Two Strings is not only as entertainment but also as a representative of deep social criticism of social movements regarding power dynamics and cultural identity. This study contributes to the field of Marxist studies by highlighting cultural dynamics and how the structure of feelings works in society to create newness without abandoning conventional traditions to achieve balance. In addition, it provides insights for future research and encourages broader exploration of increasingly diverse cultural dynamic contexts which influences the interpretation of defining culture itself. The results of this research prove that Kubo and the Two Strings (2016) represent a redefinition of Japanese culture in terms of the 3 main aspects dominant, residual, and emergent. Supported by the structure of feelings that were felt by Kubo. These findings are a powerful example of how art can serve as a tool to examine changes in culture.